Pathology of domestic animals - Jubb, K. V. F.; Kennedy, Peter C. (Peter Carleton), 1923- (Academic Press, 1963)
Pathology of Domestic Animals, Volume 1 elaborates on the bone structure and diseases, as well as the genital, circulatory, and respiratory systems, of domestic animals. The manuscript first offers information on bones, joints, and synovial structures and diseases of joints, including adaptational deformities of the skeleton, metabolic diseases of bones, necrosis and inflammation of bones, and discontinuities of bone and the healing of fractures. The text then ponders on the circulatory and respiratory systems. Discussions focus on congenital anomalies of the heart and large vessels, myocardi.